The Nutrinfo Digital Library as a pedagogical innovation in university nutrition education (Revista Innova Educación, 2025)
This study analyzed the impact of the Nutrinfo Digital Library on the level of nutrition education among students in a Faculty of Food Industries at a university in the Peruvian Amazon, located in the city of Iquitos. The research was based on a quasi-experimental design with a control group. The sample consisted of 62 students enrolled in the faculty and was divided into an experimental group (n = 31) that received the intervention and a control group (n = 31) that received no intervention, thus ensuring baseline homogeneity among participants. For data collection, a validated questionnaire was administered as a pretest and posttest to assess nutrition education, along with a survey aimed at examining perceptions and use of the digital library. Pretest results showed that, prior to the intervention, both groups were comparable, with a predominance of nutritional knowledge at the deficient level ranging from 64.5% to 71.0%. After the digital library intervention, posttest analysis revealed a significant change in the experimental group, where 41.9% of students reached the “Good” knowledge level—an improvement not observed in the control group. It is concluded that the Nutrinfo Digital Library has been validated as a functional and sustainable teaching resource capable of enhancing nutrition education in the university context. Its use resulted in a notable increase in students’ competencies, reflecting a positive and statistically significant transformation.
Keywords: digital library; educational technology; nutrition education; online learning